Oriented-lake development in the context of late Quaternary landscape evolution, McKinley Bay Coastal Plain, western Arctic Canada. (15th August 2020) - Wolfe, Stephen; Murton, Julian; Bateman, Mark; Barlow, John
Abstract: Oriented lakes—characterized by elongate forms, central basins and shallow littoral shelves—are common features of circum-arctic coastal lowlands. The environmental conditions, geological processes and chronology associated with the development of oriented lakes, however, are little known but essential for understanding how such Arctic lowlands evolve. Using combined techniques of field and drill-log stratigraphy and sedimentology, luminescence and radiocarbon dating methods and geomorphic mapping, we reconstruct the landscape evolution leading toward oriented-lake formation on the McKinley Bay Coastal Plain of western Arctic, Canada—a region with over 900 oriented lakes. Most lakes with deep central basins are inherited from a preglacial braidplain (ca. 73–27 ka) and alluvial braided-channel network that extended beyond the glacial limit (ca. 18.6–14.3 ka). Eolian erosion, active during the lateglacial and postglacial period (ca. 12.8–1.9 ka), reworked fluvial deposits. Eolian processes modified existing basins and created other shallow deflationary basins, as small barchanoid dunes migrated under cold, dry paraglacial conditions between about 12.8 and 10.7 ka. Vegetation cover developed at the onset of the early Holocene climatic optimum ca. 10.7 ka, and parabolic dunes were active between 9.6 and 4.6 ka. Thus, oriented lakes developed in basins conditioned by fluvial and eolian processes. In the absence of much near-surface ground ice, lateral expansion of deep-basin lakes and shallow stabilized deflationary basins predominated during the late Holocene through wind-induced wave and current processes. Overall, this sequence of oriented-lake formation does not support a thaw-lake cycle but, rather, small-basin evolution of a periglacial landscape. Highlights: McKinley Bay Coastal Plain in western Arctic Canada contains >900 oriented lakes. Landscape evolution since ∼73 ka included fluvial, eolian and ice-marginal processes. Ground ice is insufficient for lake-basin initiation by thermokarst subsidence. Lake basins initiated in channels of a braidplain later modified by eolian activity.